2019
DOI: 10.1091/mbc.e19-05-0286
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical mechanotransduction alters nuclear shape and mechanics via heterochromatin formation

Abstract: The nucleus houses, organizes, and protects chromatin to ensure genome integrity and proper gene expression, but how the nucleus adapts mechanically to changes in the extracellular environment is poorly understood. Recent studies have revealed that extracellular physical stresses induce chromatin compaction via mechanotransductive processes. We report that increased extracellular multivalent cations lead to increased heterochromatin levels through activation of mechanosensitive ion channels (MSCs), without lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
103
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 66 publications
(93 reference statements)
15
103
3
Order By: Relevance
“…Increased amounts of heterochromatin lead to increased elastic stiffness [32]: if the heterochromatic B regions were liquid, there would be no change in elasticity. Experiments demonstrating that the nuclear envelope is stabilized (destabilized) against spontaneous rupture by increased (decreased) heterochromatinization further support this conclusion [33].…”
Section: Liquid Versus Solid Versus Something In Betweenmentioning
confidence: 80%
“…Increased amounts of heterochromatin lead to increased elastic stiffness [32]: if the heterochromatic B regions were liquid, there would be no change in elasticity. Experiments demonstrating that the nuclear envelope is stabilized (destabilized) against spontaneous rupture by increased (decreased) heterochromatinization further support this conclusion [33].…”
Section: Liquid Versus Solid Versus Something In Betweenmentioning
confidence: 80%
“…Our results demonstrate the dynamical equivalence between the diffusing behavior of the chromatin granules tracked in both isolated and in situ nuclei; although MPT-SURF analysis determined that osmotic stress in living cells promoted smaller mechanical changes than in isolated nuclei. Probably, this is due to regulation mechanisms in the whole cell, through mechanosensitive ion channels able to regulate the nuclear compaction and heterochromatin formation due to changes in the composition of the extracellular medium 41 . Also, we cannot discard the contribution of the cytoskeleton in living cells, which is a major actor in nuclear deformation and strain recovery 56 .…”
Section: Discussionmentioning
confidence: 99%
“…3a). To address whether these osmotic effects on intact cells might promote in situ nuclear changes detected by MPT-SURF, we cultured Jurkat cells in high (Mg 2+ ) or low (EDTA) levels of divalent cations, which have been reported to increase heterochromatin levels in breast cancer cells 41 . Firstly, we demonstrated that www.nature.com/scientificreports www.nature.com/scientificreports/ Mg 2+ addition did not alter the nuclear area of Jurkat cells, whilst EDTA treatment significantly increased it (Fig.…”
Section: Chromatin Mobility By Multiple Particle Tracking Enhanced Upmentioning
confidence: 99%
“…In addition to the cellular mechanical support, lamins cover a multitude of other functions, related to chromatin organization, gene regulation, and cell fate determination. The substrate stiffness correlates to the amount of A-type lamins and the phenotype of the cells [154,156,157]. For example, Heo et al showed that compliant external stimuli favor the MSC differentiation into adipocytes, induced by scarce cell focal adhesions and therefore, soft nuclei and inhibited A-type lamin production [157].…”
Section: Lamin A/c Roles In Cell Mechanotransductionmentioning
confidence: 99%